Stalking the Wild Sweetgrass Domestication and Horticulture of the Grass Used in African-American Coiled Basketry - Dufault, Robert J. (SpringerBriefs in Plant Science, 2013)
Stalking the Wild Sweetgrass: Domestication and Horticulture of the Grass Used in African-American Coiled Basketry is concerned with the historical domestication of sweetgrass, the main construction/structural grass used in the three century old African-American tradition of coiled basketry in South Carolina. During the plantation era in southern agriculture, sweetgrass baskets were made for post-harvest processing and storage of rice by enslaved Africans from Lower Cape Fear, North Carolina to northern Florida. Enslaved Africans from the Rice Kingdom in Africa were prized for the basketry and rice agronomic skills and were specially sought by slavery traders. Today, this ancient craft still thrives in the community of Mt. Pleasant, South Carolina. Authored by one of the most renowned experts in the field and filled with illuminating color photographs, this volume provides knowledge of the horticulture of an extremely important wild plant and an example of the perils of plant- and people-based research and experimentation. As one of the few authoritative texts on the subject, Stalking the Wild Sweetgrass: Domestication and Horticulture of the Grass Used in African-American Coiled Basketry is a resourceful volume on wild sweetgrass, suitable for researchers and students alike.